Comparison of Clinician‐ and Self‐Assessments of Posttraumatic Stress Symptoms in Older Versus Younger Veterans. Issue 2 (2nd April 2014) - Lunney, Carole A.; Schnurr, Paula P.; Cook, Joan M.
<x xml:space="preserve">Abstract</x> Assessment of posttraumatic stress disorder (PTSD) in older adults has received limited investigation. The purpose of this study was to compare the severity of PTSD symptoms in treatment‐seeking older and younger U.S. veterans with PTSD. Participants were 360 male and 284 female veterans enrolled in 2 separate clinical trials of psychotherapy for PTSD. About 4% of the participants were age 60 years or older. Symptoms were assessed before treatment using clinician‐rated and self‐report measures. For men, only numbing symptoms were lower in older veterans; this was so in clinician ratings, d = 0.76, and self‐reports, d = 0.65. For women, clinician‐rated hyperarousal symptoms were lower in older veterans, d = 0.57. Clinician‐rated and self‐reported symptoms were strongly related, Bs = 0.95 and 0.80 in the male and female samples, respectively. Among men, clinician‐rated and self‐reported reexperiencing and hyperarousal symptoms were associated only in younger veterans. Accurate assessment of PTSD symptoms in older adults is essential to identifying and implementing effective treatment. Our findings suggest that some symptoms may be lower in older men, and that some symptoms of PTSD may be underdetected in older women. Future research should assess the combined effect of gender and age on PTSD symptom presentation.